Carolinda Clatter! - Gerstein, Mordicai (New Milford, Conn. : Roaring Book Press, 2005)
The excessively quiet town of Pupickton and the sleeping lovesick giant upon which it was built, are both awakened by the joyful noise of a little girl's songs.
Booklist starred
Kirkus Starred
Horn Book
2.2
K-3
Keywords: Giants -- Juvenile fiction; Moon -- Juvenile fiction; Noise -- Juvenile fiction; Singing -- Juvenile fiction; Giants -- Fiction; Moon -- Fiction; Noise -- Fiction; Singing -- Fiction; Giants -- Fiction; Moon -- Fiction; Noise -- Fiction; Singing -- Fiction